Design and development of prototype carpal wrist cold gas propulsion system for attitude control applications. Issue 1 (March 2020) - Alvarez, J; Tan, M; Apolinar, M; Ong, W; Alemania, T; Augusto, G; Gan Lim, L
Abstract: In recent years, the Philippine space program has launched several small-scale satellites, and lately has commissioned its own space program. Research on improving the subsystems of these satellites would be beneficial to future space programs in the Philippines. This paper will detail the process of designing, validating, fabricating, and testing a prototype Carpal Wrist Cold Gas Propulsion System (CW-CGPS). By making use of a carpal wrist's (CW) hemispherical movement capabilities, the sixteen thrusters could theoretically be replaced by four mounted on opposite ends. Optimization of the propulsion system is based on finding the nozzle design with the most adequate values for thrust, Mach number, and specific impulse while the CW design is validated when it can be calibrated to move as the program dictates. This study uses multiple programs to simulate and verify the design. The conditions of the testing environment are established by resources from international space organizations. Assembly and feasibility are assessed based on the results of the research. It was found that the final optimized system had a model torque of 0.247 N-m, more than enough to overcome the maximum combined influence of the gravity gradient torque of 2.34E-06 N-m and aerodynamic torque of 1.57E-25 N-m. The design, development, and test campaign for the thruster system is presented.